Perovskite / silicon laminated solar cell and preparation method and application thereof
By using methylamine acetate ionic liquid to regulate the FABr buried interface modification layer in an air environment, an efficient MAPbI2.4Br0.6 wide bandgap perovskite layer was prepared, which solved the problem of phase separation in perovskites and improved the stability and efficiency of perovskite/silicon stacked solar cells.
Patent Information
- Application Number
- CN202311301349.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-09
- Publication Date
- 2025-04-11
AI Technical Summary
There is a serious phase separation phenomenon in wide-bandgap perovskites, which limits the photoelectric conversion efficiency and stability of perovskite/silicon stacked solar cells.
By using methylamine acetate ionic liquid as a solvent for MAPbI2.4Br0.6 wide bandgap perovskite precursor solution in an air environment, a high-efficiency perovskite/silicon stacked solar cell is prepared.
It improves the stability and photoelectric conversion efficiency of perovskite/silicon stacked solar cells, reduces the environmental requirements of preparation, simplifies process operations, and has industrial advantages.
Smart Images

Figure CN119816172A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optoelectronic materials and devices, and relates to a perovskite / silicon stacked solar cell and a preparation method and application thereof. Background Art
[0002] In the face of the current energy shortage problem, using the photovoltaic effect to convert solar energy into electrical energy has become one of the important methods to meet energy needs. In recent years, photovoltaic power generation systems with solar cells as the core have achieved long-term development. The photoelectric conversion efficiency of single crystalline silicon cells, which currently dominate the photovoltaic market, has reached 26.6%, close to the theoretical limit of 29.4%. By combining narrow-bandgap subcells with wide-bandgap subcells, single-junction tandem cells with the function of fully utilizing the solar spectrum are a feasible way to break through the efficiency limit of single-junction solar cells. In recent years, organic-inorganic lead halide perovskite solar cells have been proven to be ideal top cell candidates for preparing monolithic tandem devices of crystalline silicon bottom solar cells due to their advantages such as low cost, long exciton diffusion length, adjustable bandgap and high efficiency (certified efficiency reached 25.8%). Researchers have reported perovskite / silicon tandem solar cells with a photoelectric conversion efficiency of more than 25%, and their certified efficiency has reached a world record of 33.2%. However, due to the serious phase separation phenomenon in wide-bandgap perovskites, the photoelectric conversion efficiency and stability of tandem devices are greatly limited. Studies have found that the photoinduced phase separation of wide-bandgap perovskites is closely related to interface, grain boundary defects and energy level mismatch.
[0003] In order to solve the above problems, researchers have carried out a lot of work, such as the commonly used interface engineering. Most of the research in interface engineering focuses on modifying the upper surface of wide bandgap perovskites and preparing wide bandgap perovskite layers and interface layers in a nitrogen glove box, which limits its commercial application. However, there are relatively few studies on the modification of the buried interface modification layer of wide bandgap perovskites. The submicron-scale extended defects and lead halide inhomogeneity of the buried interface modification layer hinder the improvement of device performance. Based on this, our team conducted a series of studies to find a more effective way to solve these problems. Summary of the invention
[0004] The present invention proposes a perovskite / silicon stacked solar cell and a preparation method and application thereof. The present invention mainly uses a green solvent methylammonium acetate ionic liquid solvent as a precursor solvent, and prepares MAPbI by regulating the FABr buried bottom interface modification layer of the perovskite in an air environment. 2.4 Br 0.6 (MA + :CN3NH3 + )The wide-bandgap perovskite layer and its efficient perovskite / silicon tandem solar cell have improved the stability of the devices in this system to a certain extent.
[0005] This is achieved specifically through the following technical solutions:
[0006] A method for a perovskite / silicon tandem solar cell comprises: step 1: preparing MAPbI 2.4 Br 0.6 Wide bandgap perovskite precursor solution; step 2: forming a hole transport layer on the crystalline silicon subcell; step 3: forming a first interface modification layer on the side of the hole transport layer away from the crystalline silicon subcell; step 4: spin coating the MAPbI prepared in step 1 on the side of the first interface modification layer away from the first hole transport layer 2.4 Br 0.6 Wide-bandgap perovskite precursor solution, and then annealing to obtain MAPbI 2.4 Br 0.6 Wide bandgap perovskite layer; Step 5: on the MAPbI 2.4 Br 0.6 The wide bandgap perovskite layer is away from the first interface modification layer to form an electron transport layer; step 6: on the electron transport layer away from the MAPbI 2.4 Br 0.6 A second interface modification layer and a metal electrode are sequentially prepared on one side of the wide bandgap perovskite layer.
[0007] A further technical solution of the present invention is:
[0008] The MAPbI 2.4 Br 0.6 The preparation process of the wide bandgap perovskite precursor solution comprises the following steps: dissolving lead iodide, methylammonium iodide, and methylammonium bromide in methylammonium acetate, heating and stirring at 60° C. for 6-12 hours (e.g., 6, 8, 10, or 12 hours) to obtain the MAPbI 2.4 Br 0.6 Wide-bandgap perovskite precursor solutions.
[0009] A further technical solution of the present invention is:
[0010] In the precursor solution, the molar ratio of lead iodide, methylammonium iodide and methylammonium bromide is 2.5:1.5:1.
[0011] A further technical solution of the present invention is:
[0012] The MAPbI 2.4 Br 0.6 The concentration of the wide bandgap perovskite precursor solution is 400-600 mg / mL, such as 400 mg / mL, 500 mg / mL, 600 mg / mL.
[0013] A further technical solution of the present invention is:
[0014] In step 2, the hole transport material is spin-coated on the crystalline silicon sub-cell at a rotation speed of 3000-5000 rpm (such as 3000, 4000, 5000 rpm), and the spin coating time is 25-35 seconds (such as 25, 30, 35 seconds). After the spin coating, annealing is performed at 100-110° C. (such as 100, 105, 110° C.) for 8-15 minutes (such as 8, 10, 12, 15 minutes).
[0015] A further technical solution of the present invention is:
[0016] The hole transport material is P3CT-N.
[0017] A further technical solution of the present invention is:
[0018] In step 3, the first electron transport layer is formed by spin coating in an air environment and annealing after spin coating.
[0019] A further technical solution of the present invention is: the material of the first interface modification layer is FABr.
[0020] A further technical solution of the present invention is: forming the first interface modification layer comprises the following steps:
[0021] (1) Dissolve 5 mg of methylammonium bromide in 1 mL of isopropanol solution;
[0022] (2) stirring the prepared formamidinium bromide solution at room temperature at a speed of 500-600 rpm (e.g., 500 rpm, 550 rpm, 600 rpm) for 1 hour;
[0023] (3) In an air environment, 30 uL of the formamidinium bromide solution is spin-coated on the hole transport layer at a speed of 3500-5000 rpm (e.g., 3500, 4000, 4500, 5000 rpm) for 20-30 seconds (e.g., 20, 25, 30 seconds);
[0024] (4) After the spin coating, anneal at 100-110° C. (e.g., 100, 105, 110° C.) for 4-8 minutes (e.g., 4, 6, 8 minutes).
[0025] A further technical solution of the present invention is: the MAPbI in step 4 2.4 Br 0.6 The wide bandgap perovskite layer is formed by spin coating the MAPbI prepared in step 1 in an air environment. 2.4 Br 0.6 The wide bandgap perovskite precursor solution is then annealed.
[0026] A further technical solution of the present invention is: forming the MAPbI2.4 Br 0.6 The wide bandgap perovskite layer includes the following steps:
[0027] Preheat the crystalline silicon subcell to 85-95°C (e.g., 85, 90, 95°C), take the MAPbI 2.4 Br 0.6 A wide bandgap perovskite precursor is added dropwise on the side of the first interface modification layer away from the first hole transport layer, and is spin-coated in an air environment at a rotation speed of 2000-3000 rpm (e.g., 2000, 2500, 3000 rpm), and the spin coating time is 20-30 seconds (e.g., 20, 25, 30 seconds). After the spin coating, it is annealed at 100-110°C (e.g., 100, 105, 110°C) for 4-8 minutes (e.g., 4, 6, 8 minutes).
[0028] A further technical solution of the present invention is: the material of the electron transport layer is PC 61 BM.
[0029] A further technical solution of the present invention is: forming the electron transport layer comprises the following steps:
[0030] (1) Add 15 mg of PC 61 BM was dissolved in 1 mL of chlorobenzene solution;
[0031] (2) Place the configured PC 61 The BM solution is stirred at 55-65° C. (e.g., 55° C., 60° C., 65° C.) and a speed of 400-500 rpm (e.g., 400 rpm, 450 rpm, 500 rpm) for 2-3 hours (e.g., 2 hours, 3.5 hours, 3 hours);
[0032] (3) Take 30 μL of PC 61 The BM solution is spin-coated on the perovskite layer, first at a speed of 1000-1200 rpm for 50-60 seconds, and then at a speed of 1800-2000 rpm for 2-5 seconds.
[0033] A further technical solution of the present invention is:
[0034] In step 5, the second interface modification layer is formed by vacuum evaporation; preferably, the material of the second interface modification layer is BCP; more preferably, the thickness of the second interface modification layer is 1 nm.
[0035] A further technical solution of the present invention is:
[0036] The metal electrode in step 5 is formed by vacuum evaporation; preferably, the material of the metal electrode is Ag; more preferably, the thickness of the metal electrode is 100 nm.
[0037] The present invention is also achieved through the following technical solutions:
[0038] A perovskite / silicon tandem solar cell, comprising: a crystalline silicon subcell; a hole transport layer formed on the crystalline silicon subcell; a first interface modification layer formed on a side of the hole transport layer away from the crystalline silicon subcell; and a MAPbI layer formed on a side of the first interface modification layer away from the first hole transport layer. 2.4 Br 0.6 Wide bandgap perovskite layer; in the MAPbI 2.4 Br 0.6 An electron transport layer is formed on the side of the wide bandgap perovskite layer away from the first interface modification layer; on the electron transport layer away from the MAPbI 2.4 Br 0.6 A second interface modification layer and a metal electrode are sequentially formed on one side of the wide bandgap perovskite layer.
[0039] The crystalline silicon sub-cell in the present invention may include a single crystalline silicon sub-cell sheet, or may include a plurality of crystalline silicon sub-cell sheets connected in series.
[0040] This is achieved specifically through the following technical solutions:
[0041] An application of the aforementioned perovskite / silicon tandem solar cell or the perovskite / silicon tandem solar cell prepared by the aforementioned method in the field of optoelectronics.
[0042] Beneficial Effects
[0043] The present invention aims at the technical problems of energy level matching and phase separation of mixed halide wide bandgap perovskite solar cells and their sensitivity to moisture in the air. The present invention proposes a method for preparing a perovskite / silicon tandem solar cell, wherein methylammonium acetate ionic liquid is used as MAPbI 2.4 Br 0.6 Wide-bandgap perovskite precursor solution solvent, preparing efficient and stable MAPbI by regulating the FABr buried interface modification layer 2.4 Br 0.6 Wide-bandgap perovskite-silicon tandem solar cells.
[0044] Beneficial effects of the present invention:
[0045] (1) In view of the sensitivity of existing perovskite batteries to moisture in the air, the present invention proposes a MAPbI based on methylammonium acetate ionic liquid. 2.4 Br 0.6Wide bandgap perovskite precursor solution. By adjusting the ratio of I and Br in the wide bandgap perovskite precursor solution, MAPbI with the optimal bandgap range that meets the wide bandgap in perovskite / silicon tandem solar cells is prepared. 2.4 Br 0.6 Wide-bandgap perovskite precursor solutions.
[0046] (2) Existing studies require the preparation of wide-bandgap perovskite layers in a nitrogen glove box. However, the present invention does not require the preparation of wide-bandgap perovskite layers in a nitrogen environment, which greatly reduces the stringent environmental requirements for its preparation. Methylamine acetate ions can be used directly in an air environment as a perovskite precursor solvent to prepare high-efficiency wide-bandgap perovskite layers and their silicon stacked solar cells.
[0047] (3) Existing research mainly focuses on interface regulation on the upper surface of wide bandgap perovskite, and there is little research on the buried interface modification layer of wide bandgap perovskite. However, the present invention prepares a high-efficiency wide bandgap perovskite layer and its stacked solar cell by regulating the buried FABr interface modification layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a structural diagram of a wide bandgap perovskite / silicon stacked solar cell device prepared with an interface modification layer in air according to the present invention;
[0049] Figure 2 This is a SEM image of a wide bandgap perovskite layer with a large grain size prepared in the air with an interface modification layer according to the present invention;
[0050] Figure 3 is an XRD diagram of a wide bandgap perovskite layer prepared in the air with an interface modification layer according to the present invention;
[0051] Figure 4 It is a UV-vis absorption spectrum of a wide bandgap film prepared in the air by using methylamine acetate as a precursor solution solvent to control the interface modification layer;
[0052] Figure 5 It is a JV curve diagram of the wide bandgap stacked perovskite / silicon solar cell prepared in the air environment with and without the interface modification layer of the present invention. DETAILED DESCRIPTION
[0053] For a better understanding of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. Obviously, the embodiments described are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] In this embodiment, methylammonium acetate ionic liquid is used as MAPbI 2.4 Br 0.6 The perovskite precursor solution solvent is used to prepare a wide bandgap perovskite layer with low defect density and large grain size and a perovskite / silicon stacked solar cell thereof by regulating the buried interface modification layer, so as to fully understand the present invention, which mainly includes the following steps:
[0056] Step 1) Use nitrogen to blow away dust from the prepared crystalline silicon sub-cell and place it aside for future use.
[0057] Step 2) 389.6 mg of lead iodide, 53.7 mg of methylamine iodide, and 56.7 mg of methylamine bromide were weighed and dissolved in 1 mL of methylammonium acetate ionic liquid solvent at a molar ratio of 2.5:1.5:1, and stirred at 60° C. for 6-12 hours until completely dissolved to prepare a perovskite precursor solution with a concentration of 500 mg / mL.
[0058] Step 3) Dilute the 10 mg / mL P3CT-N solution to 2 mg / mL P3CT-N, using methanol as the solvent.
[0059] Step 4) 15 mg of PC 61 BM was dissolved in 1 mL of chlorobenzene solution; 61 The BM solution was stirred at 60 °C and 500 rpm for 3 h;
[0060] Take 30uL of PC 61 The BM solution was spin-coated on the perovskite layer, and the spin-coating conditions were 1000 rpm for 60 s and 2000 rpm for 2 s.
[0061] Step 5) treating the crystalline silicon subcell in step 1) with ultraviolet ozone for 15 minutes.
[0062] Step 6) Take 25 μL of hole transport material P3CT-N and drop it onto the crystalline silicon sub-cell treated in step 5), and use a spin coater to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the crystalline silicon sub-cell with P3CT-N spin-coated at 100°C for 10 minutes.
[0063] Step 7) Place the crystalline silicon subcell with the hole transport layer spun on after annealing in step 6) on a hot spin coater with a substrate temperature of 90° C. and preheat for 3 minutes.
[0064] Step 8) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the preheated crystalline silicon subcell in step 7), spin-coat it into a film, and then anneal it to form a wide-bandgap perovskite layer. The spin-coating speed of the perovskite precursor solution is 2500 rpm for 20 seconds, and anneal it in air at 100°C for 5 minutes.
[0065] Step 9) Spin-coating the electron transport layer material of step 4) onto the wide bandgap perovskite layer of step 8) under the conditions of 1000 revolutions for 60 seconds and 2000 revolutions for 2 seconds to form an electron transport layer.
[0066] Step 10) Vacuum evaporation technology is used to evaporate 1 nm BCP on the electron transport layer of step 9), and then 100 nm metal electrode Ag is evaporated, thereby obtaining a perovskite / silicon stacked solar cell.
[0067] Step 11) Under standard test conditions (AM1.5G illumination), the energy conversion efficiency of the battery device without interface modification prepared in this example was 14.32%, the open circuit voltage was 1.65V, and the short circuit current was 20.45mA / cm 2 , the filling factor is 42.52%;
[0068] Example 2
[0069] In this embodiment, methylammonium acetate ionic liquid is used as MAPbI 2.4 Br 0.6 The perovskite precursor solution solvent is used to prepare a wide bandgap perovskite layer with low defect density and large grain size and a perovskite / silicon stacked solar cell thereof by regulating the buried interface modification layer, so as to fully understand the present invention, which mainly includes the following steps:
[0070] Step 1) Use nitrogen to blow away dust from the prepared crystalline silicon sub-cell and place it aside for future use.
[0071] Step 2) 389.6 mg of lead iodide, 53.7 mg of methylamine iodide, and 56.7 mg of methylamine bromide were weighed and dissolved in 1 ml of methylammonium acetate ionic liquid solvent at a molar ratio of 2.5:1.5:1, and stirred at 60°C for 6-12 hours until completely dissolved to prepare a perovskite precursor solution with a concentration of 500 mg / mL.
[0072] Step 3) Dilute the 10 mg / mL P3CT-N solution to 2 mg / mL P3CT-N, using methanol as the solvent.
[0073] Step 4) Dissolve 5 mg of methylammonium bromide in 1 mL of isopropanol solution; stir the prepared methylammonium bromide solution at room temperature at a rotation speed of 500 rpm for 1 hour; spin-coat 30 uL of the methylammonium bromide solution on the hole transport layer at a spin coating condition of 4000 rpm for 20 seconds; anneal on a hot stage after spin coating at a condition of 100° C. for 5 minutes.
[0074] Step 5) 15 mg of PC 61 BM was dissolved in 1 mL of chlorobenzene solution;61 The BM solution was stirred at 60 °C and 500 rpm for 3 h;
[0075] Take 30uL of PC 61 The BM solution was spin-coated on the perovskite layer, and the spin-coating conditions were 1000 rpm for 60 s and 2000 rpm for 2 s.
[0076] Step 6) treating the crystalline silicon subcell in step 1) with ultraviolet ozone for 15 minutes.
[0077] Step 7) Take 25 μL of hole transport material P3CT-N and drop it onto the crystalline silicon sub-cell treated in step 6), and use a spin coater to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the crystalline silicon sub-cell with P3CT-N spin-coated at 100°C for 10 minutes.
[0078] Step 8) Spin-coat the interface modification material of formamidinium bromide in step 4) onto the hole transport layer in step 7) at 4000 rpm for 20 seconds to form a formamidinium bromide interface modification layer.
[0079] Step 9) placing the crystalline silicon subcell with the interface modification layer spun on after annealing in step 8) on a hot spin coater with a substrate temperature of 90° C. and preheating for 3 minutes.
[0080] Step 10) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the preheated crystalline silicon subcell in step 8), spin-coat it into a film, and then anneal it to form a wide bandgap perovskite layer. The spin-coating speed of the perovskite precursor solution is 2500 rpm for 20 seconds, and anneal it in air at 100°C for 5 minutes.
[0081] Step 11) Spin-coating the electron transport layer material of step 5) onto the wide bandgap perovskite layer of step 10), wherein the spin-coating conditions of the electron transport layer material are 1000 revolutions for 60 seconds and 2000 revolutions for 2 seconds, to form an electron transport layer.
[0082] Step 12) Vacuum evaporation technology is used to evaporate 1 nm BCP on the electron transport layer of step 11), and then 100 nm metal electrode Ag is evaporated to obtain a perovskite / silicon stacked solar cell.
[0083] Step 13) Under standard test conditions (AM1.5G illumination), the energy conversion efficiency of the battery device without interface modification prepared in this example was 17.06%, the open circuit voltage was 1.83V, and the short circuit current was 18.97mA / cm 2 , the filling factor is 49.16%.
[0084] Comparative Example 1
[0085] In an air environment, methylammonium acetate ionic liquid was used as the precursor solvent, and the molar ratio of lead iodide, methylammonium iodide, and methylammonium bromide was 2.5:1.5:1. The energy conversion efficiencies with and without interface modification were 17.06% and 14.32%, respectively.
[0086] The present invention regulates the interface modification layer to promote the formation of high-quality wide-bandgap perovskite film, thereby obtaining a wide-bandgap perovskite / silicon tandem solar cell with excellent efficiency (see the attached Figure 2 ).
[0087] The present invention uses methylammonium acetate ionic liquid as a wide bandgap perovskite precursor solution solvent, and prepares MAPbI in an air environment by regulating the perovskite buried interface modification layer FABr. 2.4 Br 0.6 The wide bandgap perovskite layer and its efficient perovskite / silicon tandem solar cell, the prepared wide bandgap perovskite layer has a size of micron level and a dense and smooth morphology, and the prepared perovskite device has excellent device efficiency. The wide bandgap perovskite / silicon tandem solar cell prepared by this method is simple to operate, has a high photoelectric conversion efficiency, and does not worry about the impact of the air environment on it, and has a rare industrial advantage.
[0088] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. A method for a perovskite / silicon tandem solar cell, characterized in that: include: Step 1: Preparation of MAPbI 2.4 Br 0.6 Wide-bandgap perovskite precursor solutions; Step 2: forming a hole transport layer on the crystalline silicon subcell; Step 3: forming a first interface modification layer on a side of the hole transport layer away from the crystalline silicon subcell; Step 4: Spin-coat the MAPbI prepared in step 1 on the side of the first interface modification layer away from the first hole transport layer. 2.4 Br 0.6 Wide-bandgap perovskite precursor solution, and then annealing to obtain MAPbI 2.4 Br 0.6 Wide-bandgap perovskite layers; Step 5: In the MAPbI 2.4 Br 0.6 The side of the wide bandgap perovskite layer facing away from the first interface modification layer forms an electron transport layer; Step 6: The electron transport layer turns away from the MAPbI 2.4 Br 0.6 A second interface modification layer and a metal electrode are sequentially prepared on one side of the wide bandgap perovskite layer.
2. The method according to claim 1, characterized in that The MAPbI 2.4 Br 0.6 The preparation process of the wide bandgap perovskite precursor solution comprises the following steps: dissolving lead iodide, methylamine iodide, and methylamine bromide in methylamine acetate, heating and stirring at 60° C. for 6-12 hours to obtain the MAPbI 2.4 Br 0.6 Wide-bandgap perovskite precursor solutions; Preferably, the molar ratio of lead iodide, methylammonium iodide and methylammonium bromide is 2.5:1.5:1; Preferably, the MAPbI 2.4 Br 0.6 The concentration of the wide bandgap perovskite precursor solution is 400-600 mg / mL.
3. The method according to claim 1, characterized in that In step 2, the hole transport material is deposited on the crystalline silicon subcell by spin coating at a rotation speed of 3000-5000 rpm for 25-35 seconds, and annealed at 100-110° C. for 8-15 minutes after the spin coating is completed; Preferably, the hole transport material is P3CT-N.
4. The method according to claim 1, characterized in that In step 3, the first electron transport layer is formed by spin coating in an air environment and annealing after spin coating; Preferably, the material of the first interface modification layer is FABr; More preferably, forming the first interface modification layer comprises the following steps: (1) dissolving formamidinium bromide in isopropanol solution; (2) stirring the prepared formamidinium bromide solution at room temperature at a rotation speed of 500-600 rpm for 1-2 hours; (3) In an air environment, spin-coat the formamidinium bromide solution on the hole transport layer at a speed of 3500-5000 rpm for 20-30 seconds; (4) After spin coating, anneal at 100-110°C for 4-8 minutes.
5. The method according to claim 1, characterized in that MAPbI as described in step 4 2.4 Br 0.6 The wide bandgap perovskite layer is formed by spin coating the MAPbI prepared in step 1 in an air environment. 2.4 Br 0.6 Wide-bandgap perovskite precursor solution, followed by annealing; Preferably, the MAPbI is formed 2.4 Br 0.6 The wide bandgap perovskite layer includes the following steps: Preheat the crystalline silicon subcell to 85-95°C and take the MAPbI 2.4 Br 0.6 The wide bandgap perovskite precursor is dripped on the side of the first interface modification layer away from the first hole transport layer, and is spin-coated at a speed of 2000-3000 rpm in an air environment for 20-30 seconds. After the spin coating, it is annealed at 100-110° C. for 4-8 minutes.
6. The method according to claim 1, characterized in that The material of the electron transport layer is PC 61 BM; Preferably, forming the electron transport layer comprises the following steps: (1) Connect the PC 61 BM is dissolved in chlorobenzene solution to obtain PC 61 BM solution; (2) Place the configured PC 61 The BM solution was stirred at 55-65°C and 400-500 rpm for 2-3 hours; (3) Get PC 61 The BM solution is spin-coated on the perovskite layer, first at a speed of 1000-1200 rpm for 50-60 seconds, and then at a speed of 1800-2000 rpm for 2-5 seconds.
7. The method according to claim 1, characterized in that In step 5, the second interface modification layer is formed by vacuum evaporation; preferably, the material of the second interface modification layer is BCP; more preferably, the thickness of the second interface modification layer is 1-2 nm.
8. The method according to claim 1, characterized in that The metal electrode in step 5 is formed by vacuum evaporation; preferably, the material of the metal electrode is Ag; more preferably, the thickness of the metal electrode is 100-110 nm.
9. A perovskite / silicon tandem solar cell, characterized in that: include: Crystalline silicon subcells; a hole transport layer formed on the crystalline silicon subcell; A first interface modification layer formed on a side of the hole transport layer away from the crystalline silicon subcell; The MAPbI formed on the side of the first interface modification layer away from the first hole transport layer 2.4 Br 0.6 Wide-bandgap perovskite layers; In the MAPbI 2.4 Br 0.6 An electron transport layer formed on a side of the wide bandgap perovskite layer facing away from the first interface modification layer; The electron transport layer is away from the MAPbI 2.4 Br 0.6 A second interface modification layer and a metal electrode are sequentially formed on one side of the wide bandgap perovskite layer.
10. Use of the perovskite / silicon tandem solar cell according to claim 9 or the perovskite / silicon tandem solar cell prepared by the method according to any one of claims 1 to 8 in the field of optoelectronics.